Bulky peritoneal carcinosarcoma with tiny high-grade serous carcinoma of the fallopian tube: a case report - Nakashima, Ayaka (Int Cancer Conf J, 2020)
Peritoneal carcinosarcoma is a highly aggressive and uncommon neoplasm that has carcinomatous and sarcomatous components; the malignancy rarely localizes to the omentum. We report a case of a bulky peritoneal carcinosarcoma with tiny high-grade serous carcinoma of the fallopian tube. A 60-year-old female with a huge pelvic mass (12 cm in diameter) underwent a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy for tumor debulking. Pathological findings showed minimally invasive high-grade serous carcinoma of the left fallopian tube and carcinosarcoma of the omentum. Similar p53 diffuse immunostaining in the omental carcinosarcoma and the tubal carcinoma provides evidence for a clonal relationship between the two neoplasias. This case suggests a small serous carcinoma, originating in the tubal mucosa, subsequently became implanted in the omentum and grew preferentially, converting to a carcinosarcoma at a remote site.